Long-term antipsychotic and benzodiazepine use. and brain volume changes in schizophrenia : The Northern Finland Birth Cohort 1966 study - Huhtaniska, Sanna; Jaaskelainen, Erika; Heikka, Tuomas; Moilanen, Jani S.; Lehtiniemi, Heli; Tohka, Jussi; Manjon, Jose V.; Coupe, Pierrick; Bjornholm, Lassi; Koponen, Hannu; Veijola, Juha; Isohanni, Matti; et al. (Psychiatry Research: Neuroimaging, 2019)
High doses of antipsychotics have been associated with loss in cortical and total gray matter in schizophrenia. However, previous imaging studies have not taken benzodiazepine use into account, in spite of evidence suggesting adverse effects such as cognitive impairment and increased mortality. In this Northern Finland Birth Cohort 1966 study, 69 controls and 38 individuals with schizophrenia underwent brain MRI at the ages of 34 and 43 years. At baseline, the average illness duration was over 10 years. Brain structures were delineated using an automated volumetry system, volBrain, and medication data on cumulative antipsychotic and benzodiazepine doses were collected using medical records and interviews. We used linear regression with intracranial volume and sex as covariates; illness severity was also taken into account. Though both medication doses associated to volumetric changes in subcortical structures, after adjusting for each other and the average PANSS total score, higher scan-interval antipsychotic dose associated only to volume increase in lateral ventricles and higher benzodiazepine dose associated with volume decrease in the caudate nucleus. To our knowledge, there are no previous studies reporting associations between benzodiazepine dose and brain structural changes. Further studies should focus on how these observations correspond to cognition and functioning. Peer reviewed